ANALYZE OF MOTOR SKILLS IN THE PASS AND RECEPTION OF GERONTOATLETAS GERONTOVOLEIBOL (Fiep Bulletin - online, 2011)
This research has the purpose of realize a study about motor skills of elderly athletes. The motor development has shown that to grow older healthy it's necessary to maintain ourselves active and motor skills should be part in any daily activity. The study's focus were the pass and reception skills in gerontologic volleyball, sport commonly practiced for older people. Objectives: analyze the procedures of executions in pass and reception of gerontology athletes during the games of gerontologic volleyball trough periodical shootings; propose a new training way; test a new training way. To obtaining the data was used a camera (CANON 2R 930). The sample was composed with tactical, technical and biomechanical actions of 18 female academics that participate of UFAM's adulthood, discipline gerontologic volleyball, aged 45 to 80 years. The methodology was based on three stages of filming: the first pre-training, the second during the training and the third post training. The data from the recordings were analyzed by analysis tables targeted. Thus, the results obtained during the research confirms what Spirduso (1995) apud Tani (2005) stated: the neuronal losses are a cause of slowness in performing more complex motor skills, but there was improvement in the training phase confirming the process of learning and relearning in elderly people, however erratically. We conclude that there are elderly people that have the ability to learn from new experiences offered to them.
Keywords: motor skill; the elderly; gerontovoleibol